Diagnosis: schizophrenia : a comprehensive resource for consumers, families, and helping professionals - Miller, Rachel (Social worker); Mason, Susan Elizabeth (Columbia University Press, 2011)
In this book, thirty-five young, recently diagnosed patients speak about schizophrenia and the process of recovery, while two specialists illuminate the medical science, psychoeducation, and therapeutic needs of those coping with the illness, as well as access to medical benefits and community resources. A remarkably inclusive guide, the volume informs patients, families, friends, and professionals, detailing the possible causes of schizophrenia, medications and side effects, the functioning of the brain, and the value of rehabilitation and other services. In their dialogues, participants confront shame, stigma, substance use, and relapse issues and the necessity of healthy eating, safe sex practices, and coping skills during recovery. Clinicians elaborate on the symptoms of schizophrenia, such as violent and suicidal thoughts, delusions, hallucinations, memory and concentration problems, trouble getting motivated or organized, and anxiety and mood disorders. Adopting an uplifting tone of manageability, the participants, authors, and clinicians of this volume offer more than advice; they prescribe hope.